Kansas Land Prices and Cash Rental Rates - Dhuyvetter, Kevin C.; Taylor, Mykel (My University, 2012)
This farm management guide reports Kansas land prices and cash rental rates for 1993-2012. The data is meant to be useful to farm managers.
MF1100_2012_11
Keywords: MF1100; Economics; MF